Long-Term Weight Change and Glycemic Control in Patients With Type 2 Diabetes Mellitus and Treated vs. Untreated Sleep-Disordered Breathing—Analysis From the DIAbetes COhoRtE - Schaller, Louisa; Arzt, Michael; Jung, Bettina; Böger, Carsten A.; Heid, Iris M.; Stadler, Stefan (Frontiers in Neurology, 2021)
Hypothesis: Positive airway pressure (PAP) is the standard treatment for sleep-disordered breathing (SDB), a prevalent condition in patients with type 2 diabetes mellitus (DM2). Recent studies showed that short-term PAP treatment may cause weight gain. However, long-term data for DM2 patients are scarce. Therefore, the aim of the present analysis was to assess changes in weight and glycemic control in patients with DM2 and treated versus untreated SDB. Methods: The DIACORE (DIAbetes COhoRtE) study is a prospective population-based cohort study in DM2 patients. At baseline, patients of the DIACORE-SDB sub-study were tested for SDB (defined as apnea-hypopnea-index [AHI] ≥ 15/h) using a two-channel ambulatory SDB-monitoring device. In this observational study, PAP treatment was initiated in a subgroup of patients with SDB (SDB PAP) within clinical routine between the baseline and first follow-up visit (median observation period of 2.3 [2.2;2.4] years), whereas the other patients with SDB did not receive PAP (SDB untreated). At baseline and first follow-up visit weight and HbA1c were assessed. Results: Of the 346 patients with SDB (mean age 68 years, 71% male, body-mass index (BMI) 31.9 kg/m²) 17% were in the SDB PAP and 83% in the SDB untreated group. Weight change within the observation period was similar in both groups (-0.2 kg and -0.9 kg; p=0.322). The percentage of patients with severe weight gain (≥ 5 kg) within the observation period was significantly higher in the SDB PAP group compared to the SDB untreated group (15.0% vs. 5.6%; p=0.011). Multivariable regression analysis accounting for baseline HbA1c, insulin substitution, BMI, waist-to-hip ratio, physical activity and AHI showed that PAP treatment was significantly associated with a weight gain ≥ 5 kg (OR=3.497; 95% CI [1.343; 9.106]; p=0.010) and an increase in HbA1c (B=2.410; 95% CI [0.118; 4.702]; p=0.039). Conclusion: Median weight change was similar in SDB patients with and without PAP treatment. However, patients with DM2 and PAP treatment have an increased risk of severe long-term weight gain and an increase in HbA1c.